Improving the Teaching of Arabic Through the Effective Use of YouTube - Jumah-Alaso, Salih Muhammad; Onisabi, Abdullahi Shehu (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2020)
This study examines ways of improving Arabic's teaching and learning process by applying YouTube video clips as audio-visual aids. Eighteen Arabic students in Kaduna State College of Education and Kwara State University constituted the study sample. A descriptive method with Pre-test and Post-test was conducted. Data were collected through the essay writing, translation, and structure test. The data were analyzed through the descriptive statistics of frequency (f) and percentage (%). The study findings revealed that the subjects performed better and demonstrated linguistic communicative competence in Arabic. Finally, the study recommends that YouTube videos should be integrated into the Arabic teaching-learning process.